E-GOVERNMENT SEBAGAI INOVASI PELAYANAN PUBLIK DI INDONESIA ANTARA HARAPAN DAN KENYATAAN - Choirul Saleh, Mr. (FIA UB, 2012)
One of duty and responsibility of a public sector organization is delivering its service in satisfied manner. For those purpose, a public sector institution need a modern and sophisticated Information Communication Technology (ICT)-based infrastructure to realize its duties and responsibilities. As a developing country, even though very late in its introduction of ICT, Indonesia also implemented that technology as an innovation in its delivering services activities. The objective of this paper is to describe and analyze the steps that were taken by Indonesia to make its service delivery more innovative by implementation of ICT-based public service. The paper used a case study on E-passport service. Though incomprehensive, the case study was a evidence of low result of the e-government implementation in Indonesia.